2018
DOI: 10.1108/ebhrm-03-2018-0021
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal study of antecedents of work engagement in Thailand

Abstract: PurposeThe purpose of this paper is to examine the effects of job demands, job resources and personal resources on work engagement using the job demands–resources (JD–R) model.Design/methodology/approachThe study utilized a longitudinal research design in a sample of Thai employees (n=182). The data were collected by questionnaires administered in two waves over a period of four months, and the hypotheses were tested using hierarchical regression analysis.FindingsThe results supported the negative relationship… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 99 publications
0
7
0
Order By: Relevance
“…EBHRM 8,1 and are less likely to leave the organisation (Chaudhary and Rangnekar, 2017;Harter et al, 2002;Kunte and RungRuang, 2019;Saks, 2006). Fine et al (2010) also found that employee engagement (a combination of work and organisational engagement) was negatively related to deviant work behaviours in Israel.…”
mentioning
confidence: 94%
“…EBHRM 8,1 and are less likely to leave the organisation (Chaudhary and Rangnekar, 2017;Harter et al, 2002;Kunte and RungRuang, 2019;Saks, 2006). Fine et al (2010) also found that employee engagement (a combination of work and organisational engagement) was negatively related to deviant work behaviours in Israel.…”
mentioning
confidence: 94%
“…Numerous studies suggest that different individual and contextual factors, such as chronological age [ 29 , 30 ], job tenure [ 31 , 32 ], perceived job and organizational fit [ 33 ], role clarity [ 34 , 35 , 36 ], job demands [ 37 ], job control [ 37 , 38 , 39 , 40 ], and perceived supervisor support [ 38 , 41 , 42 , 43 , 44 ] can affect individuals’ wellbeing, motivation, and behaviors at work. However, limited research has investigated the effect of age diversity climate on these aforementioned outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Although the JD-R model primarily highlights the beneficial role of job resources for enhancing work engagement, its logic also allows for the possibility that stress-inducing job demands diminish work engagement (e.g. Garcia et al, 2017; Kunte and RungRuang, 2019; Tadic et al, 2015).…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…In particular, this extension of the original JD-R framework identifies abusive supervision as a notable example of a hindrance demand, defined as ‘stressful demands that have the potential to thwart personal growth, learning, and goal attainment’, such that ‘hindrance demands should be negatively related to engagement because they result in negative emotions and passive, emotion-focused coping styles that reflect withdrawal and reduced employee engagement’ (Crawford et al, 2010: 836). Prior applications of the JD-R model show that employees’ work engagement is lower to the extent that they suffer from hindrance demands, including role conflict (Breevaart and Bakker, 2018), role ambiguity (Kunte and RungRuang, 2019) or excessive bureaucracy (Tadic et al, 2015). Consistent with prior research, we conceptualize abusive supervision as a hindrance job demand (Huang et al, 2019) and propose that it undermines job performance by influencing employees’ emotional exhaustion and work engagement.…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%